STUDI PEMBERDAYAAN WANITA TANI DALAM USAHATANI TERNAK SAPI MELALUI PROGRAM SAPTA USAHA PETERNAKAN DI KABUPATEN GROBOGAN (KASUS DI DESA SAMBIREJO KECAMATAN WIROSARI) - Suminah Suminah (Caraka Tani: Journal of Sustainable Agriculture, 2009)
The purpose of this research is: (1) to get data about profile of farmer woman characteristic which managing ox livestock farm; (2) identifying requirement, supplementary and resistor factor of farmer woman in ox livestock farm development; and (3) to formulate the appropriate effort intervention to woman in management of ox livestock farm. This research was conducted in Grobogan District, at Sambirejo village. Data obtained through observation, interview, and the group discussion. Result of this research is: first, description of farmer woman profile manage ox livestock farm covering age, formal education, non formal education, amount of ox had, and status of ownership of ox. Second, requirement, supplementary and resistor factor is known to relate at Seven Program of livestock farm i.e. election of seed, ready of woof, cage, reproduction, management, time after harvest and  marketing. Third, that farmer woman which managing ox livestock farm have big role in improving economic earnings of family, so that woman farmer require to be powered by unionized or grouping; then give them by training related to reinforcement their group, especially training of ox livestock woof ferment.